2011
DOI: 10.1183/09031936.00044411
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognised ventricular dysfunction in COPD

Abstract: While both chronic congestive heart failure (CHF) and chronic obstructive pulmonary disease (COPD) impose a substantial disease burden and share aetiological and epidemiological associations, they have largely been studied separately. The aim of our study was to assess the prevalence and the prognostic implications of the coexistence of left ventricular dysfunction in COPD patients and airway obstruction in CHF patients.We used a prospective cohort study including stable o60-yr-old patients with echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
1
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 33 publications
5
97
1
11
Order By: Relevance
“…Still fewer are the studies regarding COPD outpatients (Table 2), and the prevalence of unrecognized CHF ranges from 17% (in highly selected cohorts in whom diagnosis was adjudicated retrospectively [10]) to 20.5% [11]. In Italy, to our knowledge, no studies on CHF prevalence in COPD outpatients exist.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Still fewer are the studies regarding COPD outpatients (Table 2), and the prevalence of unrecognized CHF ranges from 17% (in highly selected cohorts in whom diagnosis was adjudicated retrospectively [10]) to 20.5% [11]. In Italy, to our knowledge, no studies on CHF prevalence in COPD outpatients exist.…”
mentioning
confidence: 96%
“…As highlighted by Table 1, few studies have systematically examined pulmonary function in stable CHF outpatients using standardized criteria, and the Abbreviation: COPD= chronic obstructive pulmonary disease; pts= patients; y= years; PFT= pulmonary function tests; HR= hazard ratio; GPs= general practitioners; CHF=chronic heart failure; MACE= major adverse cardiac event; CV=cardiovascular observed prevalence of COPD ranges from 25 [9] -37.7% [10]. Still fewer are the studies regarding COPD outpatients (Table 2), and the prevalence of unrecognized CHF ranges from 17% (in highly selected cohorts in whom diagnosis was adjudicated retrospectively [10]) to 20.5% [11].…”
mentioning
confidence: 99%
“…A recent US study showed that among 219 patients discharged from a tertiary centre with both diagnoses of COPD and HF, 82% received echocardiography, as opposed to only 36% of patients who received pulmonary function testing, which is much less expensive and time consuming than comprehensive echocardiography 16 . In their prospective REPENSAR study, Macchia et al found that only 6.5% of cardiologists and 12% of pulmonologists had certifi ed or ruled out COPD in patients with CHF, or vice versa 17 . COPD independently predicted failure of the ejection fraction of left ventricle (EFLV) assessment by echocardiography during hospital stay in the Italian TEMISTOCLE study 18 .…”
Section: Prevalence Of Coexisting Copd and Chfmentioning
confidence: 99%
“…People with COPD are more likely to have associated comorbidities [4], including ischaemic heart disease [5], hypertension [6], heart failure, diabetes [7], metabolic syndrome, osteoporosis [8], depression [9] and lung cancer [10], which increase morbidity and complicate its management [11]. Unrecognised heart failure has been reported in up to 20% of COPD patients [12,13].…”
Section: Roles and Responsibilities Of Trial Management Commiteesmentioning
confidence: 99%